2018
DOI: 10.3357/amhp.5022.2018
|View full text |Cite
|
Sign up to set email alerts
|

Acute Mild Hypoxic Hypoxia Effects on Cognitive and Simulated Aircraft Pilot Performance

Abstract: Our findings indicate a significant influence of mild HH on a number of outcome measures at altitudes above 10K, where operational restrictions are well established. In contrast, there was no clear influence of HH on performance at lower altitudes (i.e., 8K and 10K). The occurrence of HH symptoms and the decrements in target identification latency and accuracy at 8K and 10K may negatively impact flight performance and require further study.Bouak F, Vartanian O, Hofer K, Cheung B. Acute mild hypoxic hypoxia eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 0 publications
2
53
1
Order By: Relevance
“…22 Thus, the notion that decreased arterial desaturation is responsible for cognitive impairment appears to be extended to exercising under hypoxia. Both Bouak et al 28 and Shannon et al 32 have previously indicated that cognitive performance was impaired during/after exercise under severe hypoxia, but not moderate hypoxia. 28,32 These findings suggest that the severity of hypoxia is a critical factor in determining cognitive performance when acute exercise is performed in hypoxia.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…22 Thus, the notion that decreased arterial desaturation is responsible for cognitive impairment appears to be extended to exercising under hypoxia. Both Bouak et al 28 and Shannon et al 32 have previously indicated that cognitive performance was impaired during/after exercise under severe hypoxia, but not moderate hypoxia. 28,32 These findings suggest that the severity of hypoxia is a critical factor in determining cognitive performance when acute exercise is performed in hypoxia.…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, several studies demonstrated that cognitive performance was impaired during, or after, exercise in acute hypoxia. 28 30 reported impaired performance in the memory recognition and flanker task, but not in the N-back task, during exercise in severe hypoxia. Bouak et al 28 examined delayed matching-to-sample test, N-back and Stroop tasks after exercise under hypoxia at four different levels, and cognitive impairment was observed in all tasks under the most severe hypoxic environment.…”
Section: Laboratory Settingmentioning
confidence: 92%
See 3 more Smart Citations